68Ga-FAPI-04 PET/MR Versus 18F-FDG PET/CT in the Detection of Ovarian Cancer. (June 2023) - Sun, Gaofeng; Zou, Ruoyao; Yao, Liangqing; Zuo, Changjing
Abstract: A 75-year-old woman presented with right lower abdominal pain. Pelvic ultrasound showed a cystic solid mass in the right adnexa. Painless enlarged lymph nodes on the left supraclavicular side with biopsy were suggestive of metastatic cancer. 18 F-FDG PET/CT performed to evaluate the primary tumor showed intense uptake in both regions of the right adnexa and the gastric sinus, but 68 Ga-FAPI PET/MRI showed uptake only in the right adnexal region. A subsequent gastroscopic biopsy confirmed atrophic inflammation. Finally, surgery histopathology revealed ovarian cancer. This case demonstrated that 68 Ga-FAPI PET/MRI may help exclude suspected primary gastric carcinoma with false-positive 18 F-FDG uptake.